2020
DOI: 10.1136/jnnp-2020-323304
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset riboflavin transporter deficiency: a treatable mimic of various motor neuropathy aetiologies

Abstract: ObjectiveRiboflavin transporter deficiencies (RTDs), involving SLC52A3 and SLC52A2 genes, have recently been related to Brown-Vialetto-Van Laere (BVVL) syndrome, a hereditary paediatric condition associating motor neuropathy (MN) and deafness. BVVL/RTD has rarely been reported in adult patients, but is probably underdiagnosed due to poor knowledge and lack of awareness of this form of disease among neurologists. In this study, we aimed to investigate the phenotype and prognosis of RTD patients with late-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A summary of the articles that reported follow-up data in each of the domains is shown in Table S1. Forty-seven of those patients had RTD2 due to biallelic mutations in SLC52A2, [2][3][4]12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] 46 had RTD3 due to biallelic mutations in SLC52A3 18,20,24,27,31, and one patient had a mutation in both SLC52A2 and SLC52A3. 58 Seventy-six of the 94 patients (80.9%) showed an overall improvement after riboflavin supplementation, and the remaining (19.1%) were stable after riboflavin supplementation.…”
Section: Overall Responsementioning
confidence: 99%
“…A summary of the articles that reported follow-up data in each of the domains is shown in Table S1. Forty-seven of those patients had RTD2 due to biallelic mutations in SLC52A2, [2][3][4]12,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] 46 had RTD3 due to biallelic mutations in SLC52A3 18,20,24,27,31, and one patient had a mutation in both SLC52A2 and SLC52A3. 58 Seventy-six of the 94 patients (80.9%) showed an overall improvement after riboflavin supplementation, and the remaining (19.1%) were stable after riboflavin supplementation.…”
Section: Overall Responsementioning
confidence: 99%
“…Empirical studies showed that RF administration gradually improves symptoms, as muscle strength, motor function, respiration, hearing, and vision in some children affected by RTD [ 64 , 65 , 66 ]. This prompted researchers to investigate at the molecular and cellular level possible beneficial effects of RF supplementation to RTD in vivo or in vitro models.…”
Section: Therapeutic Prospects For Rtdmentioning
confidence: 99%
“…Low-cost treatments such as salbutamol or pyridostigmine can avoid sudden death or disability in the course of a long diagnostic journey. BVVL, a recessive disorder caused by a loss of function mutation in one of the three different intestinal riboflavin transporter genes, can be managed with a high dose of riboflavin [85] , and leads to severe bulbospinal atrophy in absence of treatment. Unfortunately, neither CMS not BVVL can be identified by any sensitive biomarker and are thus not amenable to NBS; identification of such disorders at birth should therefore be carried out through whole exome or targeted sequencing.…”
Section: Article In Pressmentioning
confidence: 99%